Solutrean and Magdalenian ferruginous rocks heat-treatment: accidental and/or deliberate action?. (March 2015) - Salomon, Hélène; Vignaud, Colette; Lahlil, Sophia; Menguy, Nicolas
Abstract: Heating of prehistoric coloring materials can induce radical changes in color indicative of structural matter transformation. For instance, the structure of the yellow iron oxide-rich mineral, goethite, changes into the red iron oxide-rich mineral, hematite, when it is heated to around 250–300 °C. For a long time, heating has been thought to be the reason for the high frequencies of red rocks used in camp sites and the red pigments in rock art paintings. However, records of heat-treatment of coloring materials are usually not well documented; the contextual information is not clear enough to confirm intentional heating. Two Solutrean camp sites (the flint workshop Les Maîtreaux and the hunting site Combe Saunière I) and one middle Magdalenian cave with rock art (Grotte Blanchard, La Garenne) allow us to study the heating process of ferruginous rocks. All three sites, which have been excavated relatively recently, have well-defined archaeological records and strong associations between the ferruginous rocks and other artifacts. With the use of X-ray diffraction and electron µ-diffraction for identifying structural modification and SEM-FEG and TEM-FEG for detecting dehydration nano-pores, we have strong evidence for intentional heat-treatment of yellow goethite-rich materials in two archaeological contexts and one site for unintentional heating, where rocks were only partially transformed. Intentional heating to obtain red hematite from primary goethite would have required ingenious methods of temperature control in fireplace settings and purpose-built ground ovens. Highlights: We documented intentional and accidental heating of pigment at palaeolithic sites. We evidenced planned and well-controlled intentional heating to produce red hematite. We concluded to the set-up of sophisticated procedures to heat-transform goethite.